Criteria for the introduction of a free zone from regulated harmful organisms of fruit crops - Yusko, L.; Gunchak, V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The analyzed methodical approaches to the establishment of the boundaries of free zones in the countries of distribution of the investigated organisms. The criteria for determining the boundaries of the free zone from regulated pests of fruit crops (E. amylovora and M. fructicola) taking into account their biological characteristics.